Suicide Ideation Among Justice-Involved Youth: Trauma History, Mental Disorder, and Experiences in Residential Facilities - Liu, Lin (Criminal justice policy review, 2025)
In extant suicide studies on youth in juvenile justice residential facilities, limited research attention has been dedicated to the joint effects of existing suicidality imported by an individual into a facility and the experiences in the facility. The current study conceptualized two camps of determinants of suicide among youth in juvenile justice residential facilities: risks individuals imported into a facility as well as what occurred in a facility. Using state-wide data of justice-involved youth above 8 years, the present study examined the joint effects of these predictors. Results suggested that net of the effects of traumatic childhood experiences and histories of mental disorders, the parental support youth received as well as their participation in prosocial activities in a facility neutralized the risk of suicide ideation. Furthermore, the sets of predictors of suicide ideation were not identical in different types of facilities. Implications for improving screening tools and intervention programs were discussed.